Acculturation trajectories and quality of life in South African immigrants living in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Clinical Psychology at Massey University, Palmerston North, New Zealand - Duxfield, Kara-Lise (Massey University, 2013)
Contemporary migration research using quantitative methods is limited by the use of variable-centred analysis, static measures of acculturation and a focus on negative outcomes. The current study sought to gain the benefits of both quantitative and qualitative approaches to migration research. The aim of this study was to explore the acculturation trajectories and quality of life in a group of South African immigrants living in New Zealand. The benefits of qualitative analysis were retained in the current study by a focus on case-centred rather than variable-centred analysis, incorporating a temporal perspective to capture migration experiences over time (trajectories) and using semi-structured interview data to examine individual experiences of migration. However, this study also employed quantitative analysis in the form of cluster analysis of interview data to detect shared acculturation patterns within subgroups of cases. Following this, thematic analysis was used to explore individual cases within these subgroups which were used to form profiles of shared acculturation trajectories. Participants in this study were a snowball sample of 50 South African immigrants, aged 18 years and over, who had lived in New Zealand for up to 11 years. Participants were asked to complete a one hour semi-structured interview, a short socio-demographic questionnaire and the World Health Organisation Quality of Life measure (WHOQOL-100). The interview focused on migration experiences in the pre-, early, mid and current phases of migration and the main focus of interviews was motivations for migration, employment experiences, social support, stress and coping at different phases of migration. The two primary forms of analysis in this study were profiling cases and thematic analysis. Following cluster analysis of the interview data, selected clusters were characterised using interview, quality of life and socio-demographic variables at discrete phases of the trajectory. Clusters which were exemplars of three emergent meta-themes, child-focused, social support and employment, were selected and profiles were generated and interpreted following thematic analysis. The three types of profiles generated were profiles of selected clusters of cases at discrete phases of the trajectory, primarily quantitative profiles of these same clusters of cases across the complete trajectory, and a qualitative elaboration of profiles of cases who shared similar trajectories. This study highlights the possibility of exploring both shared and idiosyncratic experiences within samples of immigrants. The profiles of acculturation trajectories highlight some important issues for South African immigrants living in New Zealand, including pre-migration contextual issues, employment experiences, financial stress, and participation in South African communities. Key findings of this study were the importance of children in motivations for migration, evidence of various levels of employment satisfaction in early migration although often employment satisfaction increased in later phases of migration, and finally this study showed important differences between Afrikaans and English-speaking South African immigrants with regards to their social support experiences and preferences. This study offers an approach to migration research which uses both quantitative and qualitative methods. In addition this study provides an alternative approach to migration research which is case-based, acknowledges the complexity and temporal aspects of acculturation, and examines the broad consequences of migration.
Keywords: Acculturation, New Zealand; South Africans in New Zealand; South African immigrants; Immigration; Migration research